Skin Cancer : Recognition and Management. - Schwartz, Robert (John Wiley & Sons, 2008)
The second edition of Skin Cancer: Recognition and Management is a definitive clinical reference which comprehensively examines the wide range of premalignant and malignant cutaneous disorders, including melanoma, Kaposi's sarcoma and other sarcomas, cutaneous lymphoma, cutaneous metastatic disease and cutaneous markers of internal malignancy, with emphasis on the most recent advances in diagnosis and management. Fully revised and expanded, this new edition now includes full colour photographs and illustrations throughout to aid recognition and diagnosis, and covers the latest developments and.